Polish revolutionary populism : a study in agrarian socialist thought from the 1830s to the 1850s - Brock, Peter, 1920-2006 (University of Toronto Press, 1977)
Polish Revolutionary Populism describes the activities and conflicting ideologies of the various organizations, abroad and in partitioned Poland, which were struggling for national independence and for agrarian and social reform.